2010
DOI: 10.3934/jimo.2010.6.895
|View full text |Cite
|
Sign up to set email alerts
|

A new exact penalty function method for continuous inequality constrained optimization problems

Abstract: In this paper, a computational approach based on a new exact penalty function method is devised for solving a class of continuous inequality constrained optimization problems. The continuous inequality constraints are first approximated by smooth function in integral form. Then, we construct a new exact penalty function, where the summation of all these approximate smooth functions in integral form, called the constraint violation, is appended to the objective function. In this way, we obtain a sequence of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 26 publications
(43 reference statements)
0
77
0
Order By: Relevance
“…The method integrates the constraints into the objective function by using several penalty parameters such that the original constrained optimization problem is transformed into an unconstrained optimization problem. It is shown that if the value of the penalty parameter is sufficiently large, then any local minimizer of the corresponding unconstrained optimization problem is a local minimizer of the original problem (Yu et al, 2010). With such a transformation, many existing methods can be utilized to deal with the unconstrained optimization problem, which makes the problem much easier to solve.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The method integrates the constraints into the objective function by using several penalty parameters such that the original constrained optimization problem is transformed into an unconstrained optimization problem. It is shown that if the value of the penalty parameter is sufficiently large, then any local minimizer of the corresponding unconstrained optimization problem is a local minimizer of the original problem (Yu et al, 2010). With such a transformation, many existing methods can be utilized to deal with the unconstrained optimization problem, which makes the problem much easier to solve.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…It is suggested that future research in construction scheduling should consider the application of the exact penalty function method for constrained optimization problems (Yu et al, 2010). The method integrates the constraints into the objective function by using several penalty parameters such that the original constrained optimization problem is transformed into an unconstrained optimization problem.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…PSO, as a type of simple and effective random searching algorithm, may lead to better results than the gradient descent method, penalty function method, and genetic algorithm, when solving some non-linear optimization problems [34,35].…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…There exist also recent works in the field of exact penalty methods for various types of optimal control problem [24][25][26][27][28][29]. These methods are of particular interest because each solution of the sequence of optimal control problem is easily computed using classical stationarity conditions of the solution.…”
Section: Introductionmentioning
confidence: 99%